Assessing effects of a plant-derived pesticide on Tetranychus urticae, Botrytis cinerea and Bombus impatiens - Gaudet, Kayla; Faraone, Nicoletta; Hillier, N. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2023)
Tetranychus urticae Koch (two-spotted spider mite) is an agricultural pest with a host range of over 1100 species of plants. Tetranychus urticae has rapidly developed resistance to a variety of synthetic chemical pesticides due to its high fecundity and short generation time. Plant essential oils have been recognized as a novel natural source of pest control that have a reduced impact to the environment and human health compared to synthetic pesticide application, and which may provide a viable alternative for managing T. urticae. The present study assessed the potential of a plant-derived product (product 102) as an acaricide, through topical and residual bioassays on a variety of plant species including common bean plant (Phaseolus vulgaris L.), lettuce (Lactuca sativa L.), tomato (Solanum lycopersicum L.), kale (Brassica oleracea L.), cucumber (Cucumis sativus L.), hops (Humulus lupulus L.) and hemp (Cannabis sativa L.). The results of our study indicate that C. sativa is not a suitable plant to host T. urticae. Product 102 was determined to be effective at preventing the growth of two known fungal species of economic concern (Cladosporium herbarum Persoon and Botrytis cinerea Persoon). By conducting acute contact toxicity tests, we also determined that product 102 is significantly less toxic to Bombus impatiens Cresson compared to the commonly used synthetic insecticide imidacloprid.